Attenuated but not virulent pseudorabies virus activates porcine bone marrow-derived dendritic cells - Emily C. Ashley; Walter Fuchs; Barbara G. Klupp; Dirk Werling; Simon P. Graham; Jane C. Edwards (Veterinary Immunology and Immunopathology, 2025)

Methane flux from Beringian coastal wetlands for the past 20,000 years - Matthias Fuchs; Miriam C. Jones; Evan J. Gowan; Steve Frolking; Katey Walter Anthony; Guido Grosse; Benjamin M. Jones; Jonathan A. O'Donnell; Laura Brosius; Claire Treat (Quaternary Science Reviews, 2024)

Immunophenotype investigation in feline intestinal non-B-cell lymphoma - Birgitt Wolfesberger; Gabriele Gradner; Barbara C. Rütgen; Katharina M. Hittmair; Ingrid Walter; Taryn A. Donovan; Miriam Kleiter; Alexander Krischak; Iwan A. Burgener; Andrea Fuchs-Baumgartinger (Journal of Comparative Pathology, 2024)

Lipid droplets and perilipins in canine osteosarcoma. Investigations on tumor tissue, 2D and 3D cell culture models - N. Leitner; J. Hlavatý; R. Ertl; S. Gabner; A. Fuchs-Baumgartinger; Ingrid Walter (Veterinary Research Communications, 2022)
Lipid droplets were identified as important players in biological processes of various tumor types. With emphasis on lipid droplet-coating proteins (perilipins, PLINs), this study intended to shed light on the presence and formation of lipid droplets in canine osteosarcoma. For this purpose, canine osteosarcoma tissue samples ( n = 11) were analyzed via immunohistochemistry and electron microscopy for lipid droplets and lipid droplet-coating proteins (PLINs). Additionally, we used the canine osteosarcoma cell lines D-17 and COS4288 in 2D monolayer and 3D spheroid (cultivated for 7, 14, and 21 days) in vitro models, and further analyzed the samples by means of histochemistry, immunofluorescence, molecular biological techniques (RT-qPCR, Western Blot) and electron microscopical imaging. Lipid droplets, PLIN2, and PLIN3 were detected in osteosarcoma tissue samples as well as in 2D and 3D cultivated D-17 and COS4288 cells. In spheroids, specific distribution patterns of lipid droplets and perilipins were identified, taking into consideration cell line specific zonal apportionment. Upon external lipid supplementation (oleic acid), a rise of lipid droplet amount accompanied with an increase of PLIN2 expression was observed. Detailed electron microscopical analyzes revealed that lipid droplet sizes in tumor tissue were comparable to that of 3D spheroid models. Moreover, the biggest lipid droplets were found in the central zone of the spheroids at all sampling time-points, reaching their maximum size at 21 days. Thus, the 3D spheroids can be considered as a relevant in vitro model for further studies focusing on lipid droplets biology and function in osteosarcoma.

HIV-related drivers of sexual compulsivity and sexuality in sexual minority men who use methamphetamine - Hema R. Kondur; Tae K. Lee; Roger McIntosh; Hetta Gouse; Robert Paul; Christian Grov; Dietmar Fuchs; Walter Gómez; Samantha E. Dilworth; Torsten B. Neilands; Adam W. Carrico (Journal of NeuroVirology, 2022)

A prospective study of oral contraceptive use and colorectal adenomas - Brittany M. Charlton; Edward Giovannucci; Charles S. Fuchs; Andrew T. Chan; Jung Eun Lee; Yin Cao; Stacey A. Missmer; Bernard A. Rosner; Susan E. Hankinson; Walter Willett; Kana Wu; Karin B. Michels (Cancer Causes & Control, 2016)

Identification of structural proteins of koi herpesvirus - Walter Fuchs; Harald Granzow; Malte Dauber; Dieter Fichtner; Thomas C. Mettenleiter (Archives of Virology, 2014)

CXCR4 antibody treatment suppresses metastatic spread to the lung of intratibial human osteosarcoma xenografts in mice - Patrick Brennecke; Matthias J. E. Arlt; Carmen Campanile; Knut Husmann; Ana Gvozdenovic; Tiziana Apuzzo; Marcus Thelen; Walter Born; Bruno Fuchs (Clinical & Experimental Metastasis, 2014)

Prospective cohort studies of bowel movement frequency and laxative use and colorectal cancer incidence in US women and men - Xuehong Zhang; Kana Wu; Eunyoung Cho; Jing Ma; Andrew T. Chan; Xiang Gao; Walter C. Willett; Charles S. Fuchs; Edward L. Giovannucci (Cancer Causes & Control, 2013)

Effect of the CYP3A inhibitor ketoconazole on the PXR-mediated induction of CYP3A activity - Ines Fuchs; Verena Hafner-Blumenstiel; Christoph Markert; Jürgen Burhenne; Johanna Weiss; Walter Emil Haefeli; Gerd Mikus (European Journal of Clinical Pharmacology, 2013)

Broad geographical distribution and high genetic diversity of shrew-borne Seewis hantavirus in Central Europe - Mathias Schlegel; Lukáš Radosa; Ulrike M. Rosenfeld; Sabrina Schmidt; Cornelia Triebenbacher; Paul-Walter Löhr; Dieter Fuchs; Marta Heroldová; Eva Jánová; Michal Stanko; Ladislav Mošanský; Jana Fričová; et al. (Virus Genes, 2012)

Plasma folate, methylenetetrahydrofolate reductase (MTHFR), and colorectal cancer risk in three large nested case–control studies - Jung Eun Lee; Esther K. Wei; Charles S. Fuchs; David J. Hunter; I-Min Lee; Jacob Selhub; Meir J. Stampfer; Walter C. Willett; Jing Ma; Edward Giovannucci (Cancer Causes & Control, 2012)

A prospective study of intakes of zinc and heme iron and colorectal cancer risk in men and women - Xuehong Zhang; Edward L. Giovannucci; Stephanie A. Smith-Warner; Kana Wu; Charles S. Fuchs; Michael Pollak; Walter C. Willett; Jing Ma (Cancer Causes & Control, 2011)

A quantitative vulnerability function for fluvial sediment transport - Reinhold Totschnig; Walter Sedlacek; Sven Fuchs (Natural Hazards, 2011)

Generation and characterization of koi herpesvirus recombinants lacking viral enzymes of nucleotide metabolism - Walter Fuchs; Dieter Fichtner; Sven M. Bergmann; Thomas C. Mettenleiter (Archives of Virology, 2011)

Total antioxidant capacity intake and colorectal cancer risk in the Health Professionals Follow-up Study - Rania A. Mekary; Kana Wu; Edward Giovannucci; Laura Sampson; Charles Fuchs; Donna Spiegelman; Walter C. Willett; Stephanie A. Smith-Warner (Cancer Causes & Control, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A Prospective Study of Body Mass Index, Hypertension, and Smoking and the Risk of Renal Cell Carcinoma (United States) - Keith T. Flaherty; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Frank E. Speizer; Walter C. Willett; Gary C. Curhan (Cancer Causes & Control, 2005)

Dietary patterns and risk of colon cancer and adenoma in a cohort of men (United States) - Kana Wu; Frank B. Hu; Charles Fuchs; Eric B. Rimm; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2004)

MouseNet© database: digital management of a large-scale mutagenesis project - Walter Pargent; Stephan Heffner; Karlheinz F. Schäble; Dian Soewarto; Helmut Fuchs; Martin Hrabé de Angelis (Mammalian Genome, 2000)

The clinical-chemical screen in the Munich ENU Mouse Mutagenesis Project: screening for clinically relevant phenotypes - Birgit Rathkolb; Tanja Decker; Edith Fuchs; Dian Soewarto; Christiane Fella; Stephan Heffner; Walter Pargent; Rüdiger Wanke; Rudi Balling; Martin Hrabé de Angelis; Helmut J. Kolb; Eckhard Wolf (Mammalian Genome, 2000)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)